2013
DOI: 10.1186/1475-2875-12-310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of antifolate and chloroquine drug resistance markers in Plasmodium vivax across Pakistan

Abstract: BackgroundPlasmodium vivax is the most prevalent malaria species in Pakistan, with a distribution that coincides with Plasmodium falciparum in many parts of the country. Both species are likely exposed to drug pressure from a number of anti-malarials including chloroquine, sulphadoxine-pyrimethamine (SP), and artemisinin combination therapy, yet little is known regarding the effects of drug pressure on parasite genes associated with drug resistance. The aims of this study were to determine the prevalence of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 60 publications
13
14
1
Order By: Relevance
“…Our observation corroborates the previous reports from Pakistan, Nepal, and Sudan. [39][40][41] However, no triple/quadruple mutations were detected, which is in contrast with previous findings from India 16,36 as India has different degrees of malaria endemicity, and the levels of mutations from the different geographical state is also varied. 42 With regard to the Pvdhps gene, majority of our isolates (77.2%) carried wild type alleles and frequency of single mutant (383G) and double mutant genotypes (383G/553G) was 10.2% and 12.6%, respectively, which have been found to be directly related to sulphadoxine resistance 43 and associated with reduced sensitivity to both sulfa drugs and sulfones.…”
Section: Discussioncontrasting
confidence: 98%
“…Our observation corroborates the previous reports from Pakistan, Nepal, and Sudan. [39][40][41] However, no triple/quadruple mutations were detected, which is in contrast with previous findings from India 16,36 as India has different degrees of malaria endemicity, and the levels of mutations from the different geographical state is also varied. 42 With regard to the Pvdhps gene, majority of our isolates (77.2%) carried wild type alleles and frequency of single mutant (383G) and double mutant genotypes (383G/553G) was 10.2% and 12.6%, respectively, which have been found to be directly related to sulphadoxine resistance 43 and associated with reduced sensitivity to both sulfa drugs and sulfones.…”
Section: Discussioncontrasting
confidence: 98%
“…In addition, the high prevalence of the L1076 mutation in the South Asian region was consistent with other recent studies in India and Pakistan with respective mutations of 54.5% and 98.0% [34,35]. Only two isolates carried the F976:L1076 mutations in the Indian study [34], whereas the previous study in Pakistan did not find either the F976 mutation or the F976:L1076 mutations [35]. Furthermore, if the hypothesis of a two-step mutation trajectory is true, then the L1076 mutation occurs first, followed by the F976 mutation before the emergence of chloroquine resistance [17,36,37].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that there was a rise in the number of chloroquine resistance markers since the first reported case of resistant P. vivax in the region, even though chloroquine has not been recommended in the antimalarial drug policy since 2009 [33]. In addition, the high prevalence of the L1076 mutation in the South Asian region was consistent with other recent studies in India and Pakistan with respective mutations of 54.5% and 98.0% [34,35]. Only two isolates carried the F976:L1076 mutations in the Indian study [34], whereas the previous study in Pakistan did not find either the F976 mutation or the F976:L1076 mutations [35].…”
Section: Discussionsupporting
confidence: 87%
“…Subsequent work has consistently shown that F57L/I (TT A / A T A ), S58R (AG A ), S117N/T (A A C/A C C) single mutations and S58R (AG A ) /S117N/T (A A C/A C C) double mutations are widely distributed in different geographical regions of south Asia (Auliff et al, 2006; Brega et al, 2004; de Pecoulas et al, 1998; Hastings et al, 2005; Imwong et al, 2003; Kaur et al, 2006; Kuesap et al, 2011; Lu et al, 2012; Mint Lekweiry et al, 2012; Ranjitkar et al, 2011; Schunk et al, 2006). Previous studies in Pakistan have shown that the S58R (AG A )/S117N (A A C) double mutation and S117N (A A C) single mutation conferring pyrimethamine resistance were present in different cities of the Punjab, Sindh and KPK provinces (Khattak et al, 2013; Zakeri et al, 2011). In the present study, the S58R (AG A )/ S117N (A A C) double mutation was also present in 10/38 populations.…”
Section: Discussionmentioning
confidence: 99%